1994
DOI: 10.1108/09654289410064381
|View full text |Cite
|
Sign up to set email alerts
|

Children Who Have No Breakfast

Abstract: Considers the importance of breakfast in relation to maintaining concentration at school and optimum growth, as well as in protecting against coronary heart disease in the future. Provides a description of a survey of five‐to eight‐year‐olds in seven inner‐city low income schools in Southampton where 5 per cent of children were found to have no breakfast. Only 20 per cent of children had a satisfactory breakfast in terms of protein and energy requirements – the most common satisfactory breakfast being cereal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…One study published in 1994 found that one-third of British school-aged children had nothing to drink prior to the beginning of the school day, reflecting a fluid fast of over 12 hours. 15 Since then, several programs have been instituted in the United Kingdom to promote adequate water intake in schoolchildren. 16,17 Research suggests that, especially at the beginning of the season, young athletes are at particular risk for dehydration due to lack of acclimatization to weather conditions or suddenly increased activity levels.…”
Section: Hydration and Physical Activity In Childrenmentioning
confidence: 99%
“…One study published in 1994 found that one-third of British school-aged children had nothing to drink prior to the beginning of the school day, reflecting a fluid fast of over 12 hours. 15 Since then, several programs have been instituted in the United Kingdom to promote adequate water intake in schoolchildren. 16,17 Research suggests that, especially at the beginning of the season, young athletes are at particular risk for dehydration due to lack of acclimatization to weather conditions or suddenly increased activity levels.…”
Section: Hydration and Physical Activity In Childrenmentioning
confidence: 99%
“…The method is appropriate for a broad range of ages and abilities, with the potential for children to adapt the style of drawing, or the drawing/writing balance, to suit their personal communication preferences. In addition, 'draw and write' has proved to be effective in facilitating participation for those who do not speak English (Box and Landman, 1994), or who have disabilities (Pridmore, 1996). In general, 'draw and write' is regarded by researchers as providing an acceptable and enjoyable means of participation for many children (Bendelow et al, 1996;Bradding and Horstman, 1999).…”
Section: Why Researchers Use 'Draw and Write'mentioning
confidence: 99%
“…It has been noted that 'the emphasis has been methodological techniques and practical and ethical issues at the expense of epistemological and analytical concerns' (Backett-Milburn and McKie, 1999). Within the literature some researchers address the problem of analysis (Horstman et al, 2008), but in many cases the analytical process is implied rather than explicit, or there is ambiguity regarding whether the art, or text, or both has been used (Box and Landman, 1994;Byrne, 1999;Mulvihill et al, 2000). It seems likely that analysis of 'draw and write' data is problematic for many researchers because it involves scrutinising artwork (Backett-Milburn and McKie, 1999).…”
Section: The 'Thorny Issue' Of Analysismentioning
confidence: 99%
See 2 more Smart Citations